Characterization of T cells in the progression of dry eye disease using single-cell RNA sequencing in mice - Zhizhi Zhang; Liwei Zhang; Baihua Chen (European Journal of Medical Research)
Abstract Background Increasing evidence indicated that T cells have significant effects in dry eye disease (DED). However, the regulatory role of T cells in DED remains unclear. Methods In this study, we examined immune responses throughout the progression in murine DED model. Using cytometry by time-of-flight (CyTOF) and single-cell RNA sequencing (scRNA-seq), we observed dynamic alterations in the proportions of immune cell landscape. Pseudotime trajectory and cell–cell communication analyses further illustrated T-cell differentiation and interaction networks. Results CD4+ and CD8+ T cells exhibited an initial decline on Day 3 (D3) and followed by a recovery on Day 7 (D7). Single-cell transcriptomics provided insights into 15 distinct subsets of T cells with heterogeneous functional states. Pseudotime trajectory analysis demonstrated coordinated differentiation patterns of CD4+ and CD8+ T cells, indicating their collaborative involvement in the inflammatory process. Conclusions Our results clarify the dynamics of the adaptive immune response in DED and indicate that targeting T cells may serve as a promising immune-modulatory approach in the treatment of DED model.